Effect of topical administration of propolis in chronic periodontitis - Nakao, Ryoma; Senpuku, Hidenobu; Ohnishi, Makoto; Takai, Hideki; Ogata, Yorimasa (Odontology, 2020)
[Abstract] To investigate the effect of topical administration of propolis (a honeybee product) or curry leaf (an herbal product) into the periodontal pockets of periodontitis patients, a double-blind controlled clinical trial was conducted with 24 subjects including one drop-out diagnosed with moderate-to-advanced chronic periodontitis who completed initial periodontal therapy. They were randomly allocated to the following treatments : placebo, propolis, curry leaf, and minocycline. Gingival crevicular fluid (GCF) samples collected before and after the intervention were analyzed to quantify the number of total bacteria and number of six major periodontopathic bacteria by real-time PCR. Periodontitis-related clinical parameters were also analyzed. Among the six propolis-treated patients whose GCF samples were P. gingivalis-positive, three patients converted to be P. gingivalis-negative after the intervention. The minocycline-treated group exhibited a decrease in probing pocket depth (PPD) with statistically significant improvement, but not gain of clinical attachment level (CAL). Both PPD and CAL have been improved in the propolis-treated group at a statistically significant level, but not the curry leaf-treated group. In conclusion, treatment with propolis significantly improved both PPD and CAL, together with a tendency towards reduced P. gingivalis burden in GCF. It is likely that a propolis-based therapy becomes an alternative treatment option for chronic periodontitis during supportive periodontal therapy.